Pelleting and sodium monensin increase milk CLA concentration from dairy cows fed flaxseed - Vieira Romero, Jakeline; De Marchi, Francilaine Eloise; Alcalde, Claudete Regina; Cecato, Ulysses; Grande, Paula Adriana; Valloto, Altair Antônio; Silva-Kazama, Daniele Cristina; dos Santos, Geraldo Tadeu (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Demand for naturally enriched foods is increasing worldwide. Animal nutrition allows incorporating nutraceutical molecules into milk. These molecules are intended for improving human health. Objective: To evaluate the effects of pelleting and monensin addition to the diet on intake, digestibility of dry matter (DM) and nutrients, milk yield and composition, and fatty acids (FA) profile in cows kept on pasture and supplemented with concentrate containing ground flaxseed (GF). Methods: Four Holstein cows were assigned to the following treatments: 1) concentrate with GF; 2) GF + 32.93 mg/Kg monensin (GFM); 3) GF pelleted (GFP); 4) GF pelleted + 32.93 mg/Kg monensin (FMP). Results: Treatments did not show effects on digestibility of dry matter (DM) and nutrients or feed intake, with the exception of ether extract intake, which was reduced by 28% with pelleting. Addition of monensin increased the conjugated linoleic acid (CLA) concentration by 47%. Pelleting increased the concentrations of CLA (70%), polyunsaturated FA (PUFA; 25%), and monounsaturated FA (MUFA; 16%), and reduced the concentrations of steric acid (C18) in 19% and total saturated FA (SFA; 14%). Conclusion: Pelleting and monensin does not alter feed intake and digestibility of DM and nutrients. Pelleting of concentrate feed containing flaxseed improves milk FA quality.